Further results on the asymptotic complexity of an iterative coding scheme - Ziv, J. (IEEE transactions on information theory, 1966)
The purpose of this paper is to demonstrate that it is possible to communicate over a memoryless channel of capacity C at any rate R < C with a probability of error less than 2^{-E(R)ν},E(R)>0 , per block of a length approximately proportional to ν^{2} and with a computational decoding complexity which is asymptotically proportional to ν^{2} when ν is large. The decoding scheme presented in this paper is based on a two-cycle iteration of a decoding procedure which has been described in an earlier paper [1 ].